LRO Camera Imaging of Potential Landing Sites in the South Pole-Aitken Basin - Jolliff, B. L.; Wiseman, S. M.; Gibson, K. E.; Lauber, C.; Robinson, M.; Gaddis, L. R.; Scholten, F.; Oberst, J.; LROC Science Operation Team (2010)
We show results of WAC (Wide Angle Camera) and NAC (Narrow Angle Camera) imaging of candidate landing sites within the South Pole-Aitken (SPA) basin of the Moon obtained by the Lunar Reconnaissance Orbiter during the first full year of operation. These images enable a greatly improved delineation of geologic units, determination of unit thicknesses and stratigraphy, and detailed surface characterization that has not been possible with previous data. WAC imaging encompasses the entire SPA basin, located within an area ranging from ~ 130-250 degrees east longitude and ~15 degrees south latitude to the South Pole, at different incidence angles, with the specific range of incidence dependent on latitude. The WAC images show morphology and surface detail at better than 100 m per pixel, with spatial coverage and quality unmatched by previous data sets. NAC images reveal details at the sub-meter pixel scale that enable new ways to evaluate the origins and stratigraphy of deposits. Key among new results is the capability to discern extents of ancient volcanic deposits that are covered by later crater ejecta (cryptomare) [see Petro et al., this conference] using new, complementary color data from Kaguya and Chandrayaan-1. Digital topographic models derived from WAC and NAC geometric stereo coverage show broad intercrater-plains areas where slopes are acceptably low for high-probability safe landing [see Archinal et al., this conference]. NAC images allow mapping and measurement of small, fresh craters that excavated boulders and thus provide information on surface roughness and depth to bedrock beneath regolith and plains deposits. We use these data to estimate deposit thickness in areas of interest for landing and potential sample collection to better understand the possible provenance of samples. Also, small regions marked by fresh impact craters and their associated boulder fields are readily identified by their bright ejecta patterns and marked as lander keep-out zones. We will show examples of LROC data including ...